Agrarian Big Push Strategy of Economic Development: An Ethiopian Example. Issue 3 (1st September 2020) - Grabowski, Richard
Abstract: This article argues that the big push strategy for economic development has generally focused on manufacturing. However, there are few empirical examples of a successful application of this strategy. Instead, a big push strategy focused on agriculture seems more likely to succeed. Such a strategy can also provide the foundation for a successful shift into manufacturing via structural change. Ethiopia is used as an example of an agricultural big push strategy. It has led to rapid growth and poverty reduction. However, it does not seem to have firmly established the conditions for successful structural change. This is mainly due to the unfinished nature of the agricultural transformation. Thus, the policy in Ethiopia needs to remain focused on agricultural productivity growth.